Live stock markets - Lambert, Clarence (My University, 1907)
Introduction: The Department of Agriculture estimated that in 1905 the aggregate number of cattle, hogs and sheep in the United States amounted to 170,000,000, and in 1906 the total value of all live stock to be about four billion dollars. In order to facilitate the handling and marketing of the enormous pordutions of live stock the large stock yards of the West are a necessity. They are the channels through which flow, practically the entire live stock output of country, and the amount of business transacted at one of these great markets reaches into the millions of dollars every year. Not only does the meat supply of our own country pass through these centers, but foreign nations depend upon us to such an extent that in 1905 they imported 224 million dollars worth of meats, both dressed and hoof. The rapid developement of the packing and their great establishments in certain cities makes sure their importance as stock markets for years to come.
Citation: Lambert, Clarence. Live stock markets. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Live Stock; Live Stock Markets; Market Management; Theses